Coherence relations in academic spoken discourse - Antonio, Juliano Desiderato (Linguistica (Ljubljana), 2012)
According to Rhetorical Structure Theory, implicit propositions emerge from the combination of pieces of text which hang together. Implicit propositions have received various labels as coherence relations, discourse relations, rhetorical relations or relational propositions. When two portions of a text hold a relation, the addressee of the text may recognize the connection even without the presence of a formal sign as a conjunction or a discourse marker. In this paper we claim that some intrinsic spoken discourse phenomena like paraphrasing, repetition, correction and parenthetical insertion hold coherence relations with other portions of discourse and, thus, may be considered strategies for the construction of coherence. The analysis, based on academic spoken discourse (five university lectures in Brazilian Portuguese), shows that these phenomena are recurring and relevant for the study of spoken discourse.
Keywords: akademski diskurz; analiza diskurza; analyse du discours; cohérence; discours académique; govorjeni jezik; koherenca; oral; portugais brésilien; portugalščina